Anti-biofilm activity of Barleria acanthoides Vahl against Methicillin-resistant Staphylococcus aureus - Pouline, S. Lourdu; Murugesan, Sathyananth; Raj, T. Leon Stephan (Current Botany, 2024)
Methicillin-resistant Staphylococcu aureus (MRSA) biofilms are notoriously difficult to treat due to their high resistance to antibiotics. This study examines the antibiofilm, antibacterial, and molecular docking potential of Barleria acanthoides ethanol extract against MRSA. A total of 18 compounds were identified in GC-MS analysis and the major compounds were beta-asarone (34.09%), Neophytadiene (15.09%) and caryophyllene (9.65%). The extract was very good at killing bacteria; at a minimum inhibitory concentration (MIC) of 0.5 mg/mL, it stopped MRSA biofilm formation by 80.07%. Molecular docking studies revealed the binding affinities of key compounds to regulatory proteins LasR and SarA, which are essential in biofilm formation and quorum sensing. These findings suggest B. acanthoides as a promising source for developing new therapeutic agents to combat MRSA biofilm-related infections.